Capital structure of Islamic banks: a critical review of theoretical and empirical research - Sakti, Muhammad Rizky Prima; Tareq, Mohamad Ali; Saiti, Buerhan; Akhtar, Tahir (Emerald Group Publishing Ltd., 2017)
Purpose – This paper critically evaluates theoretical and empirical research into capital structure practices in Islamic banks (IB) from four perspectives, namely: i) theoretical aspect and its nature, ii) determinants of capital structure in IB, iii) links between capital structure and risk management, and iv) nexus between capital structure and performance of IB. Design/methodology/approach – The authors will review and examine past studies on IB capital structure from both theoretical and empirical research. Findings – The paper concludes that most of the literature on IB capital structure is largely theoretical rather than empirical. The existing studies on IB capital structure have various limitations, which suggest a need for detailed empirical work. Detailed empirical research in the field of capital structure will support bank managers and policy makers in making decisions about improving capital structure. Originality/value – Our research will make several noteworthy contributions to address literature gaps for IB capital structure. Furthermore, this paper will identify areas for future research into capital structure practices and IB financing decisions. Lastly, this paper will equip regulators with guidelines for establishing sound capital requirements for IB.